2010
DOI: 10.1080/00224540903365430
|View full text |Cite
|
Sign up to set email alerts
|

On Coffee Talk and Break-Room Chatter: Perceptions of Women Who Gossip in the Workplace

Abstract: The present study examined perceptions of female gossipers in the workplace. Male and female participants (N=129) were asked to think of a woman who either frequently or rarely contributed negative information about other people during conversation. Participants then completed ratings on the target using the six dimensions of the FIRO-B. As predicted, high gossipers were perceived as having a greater need to exert control of others, but less need for others to control them, than low gossipers. Higher gossipers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 18 publications
1
46
1
2
Order By: Relevance
“…The researcher concluded that Watson's (2012) study andFarley et al's (2010) study might provide some insight into gossip between males and females in the workplace. However, in the current study, the researcher concluded that there was a significant difference between males and female workers gossiping in the workplace of Puerto Rico.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researcher concluded that Watson's (2012) study andFarley et al's (2010) study might provide some insight into gossip between males and females in the workplace. However, in the current study, the researcher concluded that there was a significant difference between males and female workers gossiping in the workplace of Puerto Rico.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Farley, Timme, and Hart (2010) in the United States examined the perception of female gossiper in the workplace. The study was to identify female workers as either high or low-gossipers.…”
Section: Rumors and Gossip-based On Sex And Sectormentioning
confidence: 99%
“…‫تيلة‬ ‫حت‬ ‫اما‬ ‫هو‬ ‫التنايمية‬ ‫تاظعاي‬ ‫ال‬ ‫مفهوم‬ ‫نن‬ ‫تداولف‬ ‫تع‬ ‫ما‬ ‫مال‬ ‫من‬ ‫اإلدارية‬ ‫األداياي‬ ‫اجعة‬ ‫مر‬ ‫تفل‬ ‫وك‬ ‫ة‬ ‫ستتحد‬ ‫وامل‬ ‫ستيكية‬ ‫الك‬ ‫النارية‬ ‫الكتاااي‬ ‫لتف‬ ‫ل‬ ‫مصت‬ ‫ما‬ -‫ت‬ ‫اقتت‬ ‫والتي‬ ، ‫املنامة‬ ‫نارية‬ ‫مجال‬ ‫يف‬ ‫تتتت‬ ‫ت‬ ‫نق‬ ‫ري‬ ‫التنايميتة‬ ‫البيئتة‬ ‫يف‬ ‫ومحتدداتهتا‬ ‫تاظعتاي‬ ‫تتت‬ ‫ال‬ ‫اوفتاظف‬ ‫ف‬ ِّ ‫التعري‬ (Kniffin & Wilson, 2005 Grosser et al, 2012) ‫تتت‬ ‫استتتت‬ ‫تا‬ ‫تذل‬ ‫وك‬ ، ‫تتتتتت‬ ‫ت‬ ‫تا‬ ‫ومتلقيه‬ ‫تا‬ ‫مطلقه‬ ‫من‬ ‫تا‬ ‫ك‬ ‫نق‬ ‫تا‬ ‫له‬ ‫تة‬ ‫املحتمل‬ ‫تار‬ ‫األ‬ ‫اف‬ ‫ر‬ (Waddington & Fletcher, 2005;Farley et al, 2010;Grosser et al, 2010) ‫مو‬ ، ‫تتنتاجف‬ ‫است‬ ‫تع‬ ‫ما‬ ‫نق‬ ‫تاظعاي‬ ‫ال‬ ‫مبفهوم‬ ‫املرتبطة‬ ‫اإلجتامنية‬ ‫تاي‬ ‫اس‬ ‫والدر‬ ‫املفاهيع‬ ‫اعف‬ ‫ونتاظ‬ ‫تمون‬ ‫مض‬ ‫تقاط‬ ‫اس‬ ‫مو‬ ‫دم‬ ‫من‬ ‫التعاما‬ ‫ستوج‬ ‫نارية‬ ‫ممال‬ ‫؛‬ ‫التنايمي‬ ‫الواقا‬ Mistreatment ‫املجتمعي‬ (Duffy, et al, 2002 (Tracy, 1993;DeGeus, 1997) ‫تة‬ ‫تتت‬ ‫تاق‬ ‫من‬ ‫تا‬ ‫تذل‬ ‫وك‬ ، ‫تها‬ ‫تاظتت‬ ‫تت‬ ‫ووفاظفها‬ ، ‫ري‬ ‫األ‬ ‫البحمية‬ ‫ااملجاالي‬ ‫قتها‬ ‫ون‬ ، (Wang, et al, 2010;Yang, et al, 2013 Hesketh, 1996;Hesketh, et al, 1996;Campbell, 1999;Hesketh & Neal, 1999;Ilgen & Pulakos, 1999;Murphy & Jackson, 1999;Pulakos, et al, 2000Pulakos, et al, , 2002Pulakos, et al, , 2006Koopmans, et al, 2014) . Hesketh, 1999;Griffin, et al, 2007;Johnson, 2001;Shossal, et al, 2012) .…”
unclassified
“…This study focuses on how gossip affects mainly female relationships. Farley, Timme, and Hart (2010) argue that gossip creates bonds and social ties among people. It helps individuals connect and relate to one another; it can also create some ties and points of interest between females who do not get along very well.…”
Section: Purpose Of Studymentioning
confidence: 99%
“…Gossip also gives people who gossip the higher hand in society or in groups, (Farley et al, 2010 (Dunbar, 1996(Dunbar, , 2004) that those who gossip frequently are more influential than those who gossip less, as gossip is the mechanism for keeping abreast of changes in one's social network. Researchers determined that sorority girls who gossiped the most emerged as the most influential clique in the sorority" (p. 575).…”
Section: Elements Of Gossipmentioning
confidence: 99%